Long-Term Outcome of Live Kidney Donation in South Korea - Kim, Jee Yeon (Ann Transplant, 2020)
BACKGROUND: Kidney donors may be at increased risk for end-stage renal disease (ESRD) as well as cardiovascular and all-cause mortality. In particular, data on long-term safety after kidney donation in Asian populations are lacking. We aimed to assess the safety of live kidney donation in Korean donors by using a matched control group. MATERIAL/METHODS: We conducted a retrospective cohort study using a hospital-based database (Asan Medical Center, Seoul, Korea) and a control group from the national health insurance claims database in South Korea. We analyzed the health status of 1608 kidney donors who underwent donation between September 1990 and December 2015, and we compared their characteristics with those of matched 6426 non-donors (1: 4 ratio). We also measured the glomerular filtration rate (GFR) with (51)Cr EDTA and urinary albumin excretion and assessed the prevalence of hypertension, diabetes, and general health status in 200 volunteer donors. RESULTS: Mortality was significantly lower in kidney donors compared with the matched controls (130.2 vs. 185.4 per 100,000 person-years, P=0.02). There was no significant difference in mortality if a donor had hypertension or was a current smoker at the time of donation. There was also no significant difference in ESRD (43.1 vs. 35.2 per 100,000 person-years, P=0.07) between the 2 groups regardless of hypertension and smoking status. Among the 200 donors with measured GFR, 11.5% had GFR values <60 ml/min/1.73 m(2) at 9.4±5.3 years after donation. Older age (P=0.001) and female sex (P=0.021) were significantly associated with GFR values <60 mL/min/1.73 m(2). CONCLUSIONS: Mortality and ESRD were uncommon in carefully selected kidney donors. However, donors with pre-existing risk factors should be followed up more closely to ensure long-term safety.